It's hard to share my teacher: kids have feelings, too - Prestine, Joan Singleton; Kylberg, Virginia (McGraw-Hill Children's Pub. Columbus, Ohio, 2003)
Josh is impatient while waiting his turn to show his drawing to his teacher, but he soon learns why a teacher must be shared